THE EFFECTS OF AGRICULTURRAL IRRIGATION: AN APPLICATION IN TURKEY - Mehmet Arif ŞAHİNLİ; Ahmet ÖZÇELİK (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In this study, we examined the Asartepe dam in Ankara province. Economic and social variables impact on agricultural irrigation were researched. Some variables were used as follows: usage of agricultural water, agricultural production, agricultural income, migration and etc. Primary data with related this research were taken from agricultural enterprises between 2015 and 2016 years. Simple Random Sampling (SRS) method was used to determine the selection of sample size. In this research, we had two different groups that one of them was preirrigation and the other was after irrigation group. After determining the sample size, this width of the size was 42. First strata was 31 and second strata was 11. SPSS Statistical package program was used during the data analysis environment. During the comparison between pre-irrigation group and after-irrigation group, Discriminant statistical analysis was used for.